PENDAMPINGAN PENGGUNAAN PLATFORM E-COMMERCE DALAM MENDUKUNG PROMOSI UMKM DI DESA BANYUBIRU - Yozi Aulia Rahman; Amin Pujiati; Eko Prasetyo; Avi Budi Setiawan; Nurjannah Rahayu Kristanti; Silvia Margaret; Nabila Septerika; Frida Ade Vantika (Perwira Journal of Community Development, 2026)
Micro, Small, and Medium Enterprises play a strategic role in national economic development because they are able to absorb a large number of workers. The community service activity in Banyubiru Village aims to enhance the capabilities of Micro, Small, and Medium Enterprises (MSMEs) in utilizing e-commerce platforms. The main challenges faced by MSMEs in the village, such as low digital literacy, lack of effective marketing strategies, and limited experience in using marketplaces. The method applied is Participatory Action Research (PAR), which consists of three main stages: preparation, implementation, and evaluation. The results from this activity indicate an improvement in participants' skills, ranging from understanding the appropriate platforms for their types of products, optimizing marketplace features, creating engaging visual promotional content, to realizing the importance of digital customer service. In addition, this initiative also encourages the formation of social collaboration among SMEs in managing online stores. These support programs are effective in enhancing competitiveness, strengthening brands, and expanding market access for SMEs in Banyubiru. These findings underscore that combining digital literacy with branding strategies and the use of e-commerce can be a long-term solution for the development of SMEs in the village.